Widening participation post-16: who participates? A case study of the Aim for Oxford programme - McCabe, J (2020)
Widening participation programmes at highly selective universities select their participants according to a variety of individual, area-level, and school-based indicators. Academic selection criteria also play a key role in selection at high tariff institutions, especially in post- 16 widening participation work. When contextual indicators are used ineffectively, there is a significant chance that only the most advantaged of ‘disadvantaged’ young people will have the opportunity to participate in widening participation schemes. The purpose of this study is to understand the life experiences associated with commonly used contextual indicators and explore what young people who have applied to the Aim for Oxford widening participation programme believe to have advantaged and disadvantaged them in their education. Twenty-seven young people completed a questionnaire delving into more detail about their contextual background and ten participated in semi-structured interviews to consider how they believe highly selective universities should select students onto their widening participation programmes. The study found that young people valued being selected onto widening participation programmes for their own merits as opposed to their adverse circumstances, feeling patronised by the idea of selection to meet “quotas.” Yet, the young people also recognised the role that their contextual background has played in their ambitions towards and expectations of accessing higher education. Synthesising the young people’s views, this study concludes with five recommendations for widening participation practice when selecting students, including: the use of multiple contextual indicators; prioritisation of students who might have ‘isolated knowledge’ through concurrent familial and school-based circumstances; avoidance of area-based metrics; more explicit consideration of individual circumstances not captured by indicators; and consideration of academic attainment in the context of the young person’s school.